MEMBANGUN KEMAMPUAN KOMUNIKASI MATEMATIS DALAM PEMBELAJARAN MATEMATIKA - ISTIQOMAH, FADILLAH (Jurnal Teknologi dan Bisnis, 2022)
Until now the teacher’s role in building students’ mathematical communication skills, especially in learning mathematics is still very limited. Communication ability is a very important aspect that needs to be owned by students who want to succeed in their studies. In line with that, according to Kist (Clark, 2005) effective communication skills are abilities that students need to have for all subjects. Mathematical communication skills (mathematical communication) in learning mathematics really need to be developed. This is because through mathematical communication students can organize their mathematical thinking both orally and in writing. In addition, students can also provide appropriate responses between students and the media in the learning process. Even in social interactions, someone who has good communication skills will tend to adapt more easily to anyone where he is in a community, which in turn will become a successful person in his life. In this paper, the author presents the notion of mathematical communication skills, with the scope of two things, namely students’ ability to use mathematics as a communication tool (math language), and students’ ability to communicate the mathematics learned as the content of the message that must be conveyed. How and why communication is important to build a mathematical community through open lines of communication in the classroom.